2015
DOI: 10.1515/trser-2015-0070
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Low Head Dam/Barrage on Fisheries – A Case Study of Giri River of Yamuna Basin (India)

Abstract: Shannon's diversity index H' = pi log 2 pi was calculated for 16 fish species. The index was resolved into its components, species richness and relative abundance, to determine which components played a larger role in the determination of diversity pattern. Changes in diversity were correlated with species richness (r), habitat heterogeneity, and hydrological regimes in a longitudinal stretch of 35 km along the river Giri, a major tributary of the Yamuna River system, in Western Himalayas. Abundance differs wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…The downstream section often provides increasing food resources availability and greater niche separation resulting in higher biodiversity in the aquatic system (Bhatt et al 2012;Sohail et al 2014). Also, the presence of a low-head dam in the sampling site may have restricted the upstream movement of several species resulting accumulation of taxa near the dam, affecting diversity in KA4, like Giri River of Yamuna Basin, India (Rumana et al 2015). Moreover, all the sampling sites provide a heterogeneous habitat to fish species with their riverbed comprising different materials such as pebbles, stones, gravels, and sand.…”
Section: Resultsmentioning
confidence: 99%
“…The downstream section often provides increasing food resources availability and greater niche separation resulting in higher biodiversity in the aquatic system (Bhatt et al 2012;Sohail et al 2014). Also, the presence of a low-head dam in the sampling site may have restricted the upstream movement of several species resulting accumulation of taxa near the dam, affecting diversity in KA4, like Giri River of Yamuna Basin, India (Rumana et al 2015). Moreover, all the sampling sites provide a heterogeneous habitat to fish species with their riverbed comprising different materials such as pebbles, stones, gravels, and sand.…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that the regulation of water has an impact on species richness, relative abundance and habitat heterogeneity (Rumana et al 2015;Galib et al 2018). Mohanty et al (2015) reported that greater diversity values may be because of the abundant availability of the food resources and appropriate environmental situations.…”
Section: Fish Species and Iucn Redlist Statusmentioning
confidence: 99%
“…habitat fragmentation and alteration, pollution, etc. ), and have to be supplemented with different taxa assessment and monitoring; fish being one of the most appropriate such taxa Death, 2003, 2004;Jeeva et al, 2011;Potyó and Guti, 2012;Khoshnood, 2014;Rumana et al, 2015;Bănăduc et al, 2016a;Radhi et al, 2017;Kruk et al, 2017).…”
Section: Introductionmentioning
confidence: 99%